(untitled) (The Agriculturists, 2020)
The experiment was conducted during March, 2016 to March, 2017 in a barojof experimental farm of Sher-e-Bangla Agricultural University, Dhaka. Thirteen betel vine cultivars designated as PB 001 through PB 013 were collected from different locations of Bangladesh and found remarkable variations in vegetative growth, morphological features, yield and yield attributes. The betel vine cultivars varied in vine elongation (37.46 – 50.34 cm per month), increase in internode length (6.75 – 10.08 cm per month) and vine girth (0.445 - 0.747 cm per year). The leaf length (17.13-27.35 cm), leaf breadth (8.33 - 16.20 cm), petiole length (4.83 -11.45 cm) and petiole breadth (0.47 - 0.28 cm) remarkably varied among the cultivars. Fresh weight of 100-petiole, 100-leaves, and dry matter content were 50.07 - 165.74 g, 289.38 - 565.25 g and 12.57 - 14.49%, respectively in different cultivars. Leaf number per meter vine (9.46 - 15.38) and leaf number per plant per year (50.16 - 78.44) were also varied among the cultivars. The highest annual per hectare yield was obtained from BARI Pan-1 (23.82 t) and PB 006 (23.46 t). Variations were also existed among the cultivars in vine colour, leaf colour, leaf shape, leaf tip, leaf softness and pungency of leaf of cultivars. No pungency of leaf was found in cultivars PB 006 (Misti pan). So, PB 006 (Misti pan) was seemed to be a better cultivar/ germplasm in respect of yield and quality of betel leaf. The Agriculturists 2020; 18(1) 56-65